ELECTROLYSER CONSTRUCTION SELECTION (Uzbekistan Open Conference, 2025)
Based on the results of studying the advantages and disadvantages of existing electrolyzers in the world, several of the most compact, lightweight electrolyzers were selected and manufactured, which can be installed on any passenger car and used at an electrical voltage of 12 V. During the total 12-hour operation of electrolyzers, an electrolyzer with organic glass was selected, which had the lowest water consumption, i.e., 0.051804 liters, and the highest hydrogen and oxygen yield, i.e., 88.835 liters. The maximum length of the gas flame was also the largest, i.e. 62 mm. Therefore, this electrolyzer with organic glass was chosen for further research.